MANAGEMENT OF OTOGENIC BRAIN ABSCESS - Hussain, Gulshan; Khan, Mohibullah; ullah, Saeed; ullah, Hidayat (Journal of Ayub Medical College Abbottabad, 2000)
Background: The relationship between otitis media and intracranial disease has long been established. Intracranial complications from Otitis Media can be quite devastating to the patient if an early diagnosis is not made. Brain abscess is one of the most dreadful complications of middle ear disease. The epidemiological presentation, clinical features and results of treatment are discussed in this study. Methods: This is a two years’ prospective study of 20 cases of otogenic brain abscess carried out at PGM I, LRH Peshawar. The data on history and management of these patients were collected and are reported. Results: There were 12 (60%) males and 6 (40%) females with a ratio of 3:2. Majority of the patients were teenagers; however, the age range was from 5 to 40 years. Chronic suppurative otitis media was the main cause of otogenic brain abscesses. The commonest site was cerebellum. The commonest organism isolated was proteus (20%) followed by anaerobes (15%) and pseudomonas (10%). The commonest organism reported from ear discharge was also proteus. CT scan of the brain with contrast was the investigation on which further management was based. Burr-hole aspiration was the main neurological procedure adapted in this study. There was no neurological deficit and epilepsy post operatively. Repeated aspiration was sometimes needed and recurrence was a problem (15%). Radical mastoidectomy was performed to eradicate focus of infection and make the ear safe (95%). The mortality was 10% in this study.